Differential risk factor profile of diabetes and atherosclerosis in rural, sub‐urban and urban regions of South India: The KMCH‐Non‐communicable disease studies. Issue 6 (3rd December 2020) - Velmurugan, Ganesan; Mohanraj, Sundaresan; Dhivakar, Mani; Veerasekar, Ganesh; Brag‐Gresham, Jennifer; He, Kevin; Alexander, Thomas; Cherian, Mathew; Saran, Rajiv; Pradeep, Thalappil; Swaminathan, Krishnan
Abstract: Aims: South Asia has emerged rapidly as an epicentre of non‐communicable diseases (NCDs) specifically diabetes and cardiovascular diseases. The prevalence rate, risk factors and aetiology of NCDs in different socio‐demographic settings are not clearly understood. This study was performed to assess the prevalence of diabetes and atherosclerosis and their risk factors in urban, sub‐urban and rural communities of South India. Methods: Three communities [Nallampatti (rural), Thadagam (sub‐urban) and Kalapatti (urban)] in South India were selected for participation in the KMCH‐NCD Studies. Study volunteers were administered a detailed questionnaire, underwent anthropometric measurements, clinical measurements including blood pressure, glycated haemoglobin (HbA1c ), non‐fasting lipid profile and serum creatinine. Carotid intima‐media thickness was measured using B‐mode ultrasound. Multiple logistic regression analyses were performed to understand the association of risk factors with diabetes and atherosclerosis. Results: A total of 2976 native participants, ≥20 years of age were screened. The prevalence of diabetes was 16%, 26% and 23% respectively in the rural, sub‐urban and urban study populations. Association of obesity with diabetes was observed in only urban population while hypertension and dyslipidaemia showed association in both urban and semi‐urban populations. Association of diabetes with atherosclerosis was observed in urban and semi‐urban populations. Hypertension in semi‐urban and obesity and dyslipidaemia in urban population showed association with atherosclerosis. Conclusions: Diabetes and atherosclerosis burden reported in the three different communities were higher than previous reports, especially in rural and sub‐urban regions. No traditional risk factor is identified to be associated with prevalence of diabetes and atherosclerosis in rural population. These findings suggest an urgent need for investigation into the role of non‐traditional risk factors like environmental or occupational exposures may help to better understand the aetiology of diseases in non‐urbanized communities.